Effect of Ghrelin on Caspase 3 and Bcl2 Gene Expression in H2O2 Treated Rat's Bone Marrow Stromal Cells - Alireza Abdanipour; Masoud Dadkhah; Mohsen Alipour; Hadi Feizi (Tabriz University of Medical Sciences, 2018)
Purpose: The antiapoptotic effect of ghrelin in various cell lines including bone marrow stromal cells (BMSCs) has been proved. However, the real mechanism of this effect is not clear. Caspase3 and Bcl2 are well-known pro- and antiapoptotic regulatory genes in eukaryotes. The aim of the study was to find out the effect of ghrelin on Caspase 3 and Bcl2 change in BMSCs. Methods: Rat BMSCs were cultivated in DMEM. Passage 3 BMSCs were treated with ghrelin 100 μM for 48 h. Real-time PCR for Caspase 3 and Bcl2 was carried out from B (untreated BMSCs), BH (BMSCs treated with 125 µM H2O2), BGH (BMSCs treated with 100 µM ghrelin then 125 µM H2O2) and BG (BMSCs treated with 100 µM ghrelin) groups. For immunofluorescence, cells were incubated with anti Caspase 3 and Bcl2monoclonal antibodies. Primary antibodies were visualized using the FITC method. All data are presented as means ± SEM. Values of P<0.05 were considered statistically significant. Results: Ghrelin decreased mRNA expressions of Caspase-3 significantly as compared to the BH group (P<0.05). Also, Bcl-2 gene expression showed an increment in BG group as compare with BH and BGH groups (P<0.05). A high present of Bcl-2 positive cells were observed in the BGH group while Caspase-3 positive cells were significantly decreased in the BGH group compared with the BH group (P<0.05). Conclusion: Ghrelin probably enhances BMSCs viability through regulation of pro- and antiapoptotic genes Caspase 3 and Bcl2. However the signaling pathway of this effect should be elucidated in the future.